Validation and reliability of the translated Malay version of the psychosocial impact of dental aesthetics questionnaire for adolescents - Wan Hassan, Wan Nurazreena; Mohd Yusof, Zamros Yuzadi; Shahidan, S.S.Z.; Mohd Ali, S.F.; Makhbul, M.Z.M. (BioMed Central, 2017)
Background: This paper describes the cross-cultural adaptation of the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) into Malay version (Malay PIDAQ), an oral health-related quality of life (OHRQoL) instrument specific for orthodontics for Malaysian adolescents between 12 and 17 years old.